Multicentre ISI assignment and calibration of the INR measuring range of a new point-of-care system designed for home monitoring of oral anticoagulation therapy - Leichsenring, Ingrid; Plesch, Winfried; Unkrig, Volker; Kitchen, Steve; Kitchen, Dianne P.; Maclean, Rhona; Dikkeschei, Bert; van den Besselaar, Anton M. H. P. (Thrombosis and Haemostasis, 2007)
The new CoaguChek XS system is designed for use in patient selftesting. It is the successor of the current CoaguChek S system. The detection principle is based on the amperometric measurement of the thrombin activity initiated by starting the coagulation cascade using a human recombinant thromboplastin. This study was performed to assign the International SEnsitivity Index (ISI) to the new test according to the WHO guidelines for thromboplastins and plasmas used to control anticoagulant therapy, and to establish the measuring range of the new system. At four study sites a total of 90 samples of normal donors and 291 samples of warfarin-, phenprocoumon- or acenocoumarol-treated patients were included in the study.The ISI value of the new test was assigned against the human recombinant reference thromboplastin rTF/95 at each site using the samples from stabilized patients in the International Normalized Ratio (INR) range between 1.5 and 4.5 only. The new point-of-care system’s measuring range between 0.8 and 8 INR was calibrated against the mean INR of rTF/95 and AD149 using polynomial regression. ISIs were (CV of the slope): Site 1: ISI 0.99 (1.1%); Site 2: ISI 1.02 (2.0%); Site 3: ISI 1.03 (1.1%); Site 4: ISI 1.00 (1.4%). All regression lines calculated from patient-only data pass through the normal donor data points.All CVs of the slopes of the orthogonal regression lines are well below 3%,thus fulfilling the requirements of the WHO guidelines. The mean ISI for the new CoaguChek XS PT Test is 1.01.
Keywords: INR calibration; ISI assignment; point-of-care testing; patient selftesting; CoaguChek